Otoritas Teks dan Realitas Sosial: Rekonstruksi Metodologi Pemahaman Hadis - Julaiha Julaiha; Abd. Wahid (Al-Widad, 2024)
The methodology for understanding hadith should maintain a balanced relationship between the authority of the hadith text as the normative foundation of Islamic teachings and the changing social realities in which its values are implemented. In practice, however, contemporary hadith studies remain polarized between textual approaches that prioritize the literal meaning of the text and contextual approaches that emphasize historical settings and social dynamics. This dichotomy often results in interpretations that are insufficient to address contemporary issues comprehensively. This study aims to analyze the relationship between the authority of hadith texts and changing social realities, identify the limitations of both textual and contextual approaches, and reconstruct a methodological framework that proportionally integrates textual authority with contemporary social realities. This research employs a qualitative library research design using descriptive-analytical methods supported by content analysis, comparative analysis, and conceptual synthesis of classical and contemporary literature. The findings indicate that both approaches possess significant strengths and inherent limitations, making an integrative methodology necessary. The proposed framework positions sanad criticism, matn criticism, linguistic analysis, historical context, maqāṣid al-sharī'ah, and social reality analysis as interconnected stages in understanding hadith. This integrative model is expected to preserve the authenticity and normative authority of hadith while enhancing its relevance in addressing contemporary societal challenges.